2010
DOI: 10.1007/s00540-010-0907-4
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic response following midazolam-induced general anesthesia: relationship to plasma and effect-site midazolam concentrations

Abstract: Following the induction of general anesthesia with i.v. midazolam 0.2 or 0.3 mg kg(-1), the BIS was positively correlated with the relative beta ratio. Despite a rapid decrease in the plasma and effect-site concentrations of midazolam, the average BIS remained >60 for 60 min after induction, reflecting an increased power of the electroencephalographic high-frequency band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 23 publications
3
34
0
Order By: Relevance
“…Miyake et al [ 32 ] investigated the correlation between serum concentration of midazolam and BIS index in 24 orthopedic patients (ASA I/II). Patients were separated in a small dose (0.2 mg kg −1 ) and a large dose midazolam group (0.3 mg kg −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Miyake et al [ 32 ] investigated the correlation between serum concentration of midazolam and BIS index in 24 orthopedic patients (ASA I/II). Patients were separated in a small dose (0.2 mg kg −1 ) and a large dose midazolam group (0.3 mg kg −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neural dynamics and synchronization of brain signals have been increasingly recognized to be an important mechanism to measure coordination of brain regions (Singer 2001;Xie 2010). Synchronous oscillations between different regions may be useful correlates of brain function, and their changes have been used for instance in the study of cognitive processes and depth of anesthesia (Basar et al 2001;Ferenets et al 2006;Miyake et al 2010), drug effects (Fingelkurts et al 2009;Alonso et al 2010;Minc et al 2010), pathologies directly related to cerebral activity (Jeong et al 2001;Stam 2005;Srinivasan et al 2007;Alonso et al 2011), and other diseases (Tong et al 2003;Shin et al 2006). Nonlinear techniques, mainly based on generalized and phase synchronization measures, have lately been used to quantify nonlinear interactions in neurophysiology (David et al 2004;Pereda et al 2005;Stam 2005;Stam et al 2009;Kreuz et al 2007; Montez et al 2009;Wendling et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that midazolam reduced BIS values depending on the degree of sedation. Sedation during regional anesthesia could be managed with midazolam at BIS values around 75 [5]. General anesthesia could be induced with intravenous bolus injection of midazolam 0.2-0.3 mg/kg, resulting in BIS values between 60 and 70 [6].…”
Section: Discussionmentioning
confidence: 99%